Study on the blasting vibration test of an open pit mine. Issue 1 (September 2020) - Ma, Yutao; Shi, Xiaopeng; Jin, Kaiming
Abstract: Blasting vibration is one of the important factors affecting the stability of open-pit slope. It is necessary to evaluate and analyze its harmful effect and the influence on slope stability. Blasting vibration monitoring is an effective technical means. Through the fitting analysis of enough data obtained from key location monitoring, the site coefficient K value and attenuation index α value of the monitoring range were regressed to obtain the blasting vibration attenuation law, which provided the test basis for reducing or controlling the harm of blasting vibration, and provided the basis for blasting design to promote mine safety in production.